Preparation method of fabric for grey yarn sunscreen clothes
By using hollow special-shaped spinning technology covered with modified titanium dioxide in sunscreen fabrics, the contradiction between the UV resistance and breathable and moisture-permeable properties of existing fabrics is solved, and an efficient sun protection and comfortable wearing experience is achieved.
Patent Information
- Application Number
- CN202510194436.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-21
AI Technical Summary
While improving UV resistance, existing sunscreen clothing fabrics have poor breathable and moisture permeability, which leads to uncomfortable wearing and insufficient anti-UV ability to meet the needs of high temperature seasons.
The hollow special-shaped spinning technology of coated modified titanium dioxide is adopted. By performing high-multiple drafting during the spinning process, the coated modified titanium dioxide gathers to the inner and outer surfaces of the fibers, forming a large number of convex structures, thereby improving the UV resistance and breathability of the fabric.
It achieves the long-lasting sun protection effect of the fabric, while improving breathable and moisture-permeable properties, so that the fabric can keep the skin dry during high temperature seasons and improves wear comfort.
Smart Images

Figure CN119686017A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material science and textile technology, and relates to a method for preparing raw yarn sunscreen clothing fabric. Background Art
[0002] With the popularity of outdoor sports and the improvement of people's living standards, sun protection clothing, as an important equipment to protect the skin from ultraviolet damage, has a growing market demand. The functionality of sun protection clothing is mainly reflected in its anti-ultraviolet ability, and existing sun protection clothing mainly achieves sun protection by coating anti-ultraviolet coating on the surface of the fabric. However, although this method can effectively block ultraviolet rays, it often sacrifices the breathability and moisture permeability of the fabric, making the wearer feel stuffy and uncomfortable in the hot summer. After sweating a lot, the clothes are easy to stick to the body, reducing the comfort of wearing and the sun protection effect.
[0003] At present, most common sun protection clothing fabrics are made of synthetic fibers such as polyester, and the purpose of sun protection is achieved by adding an anti-ultraviolet coating during the finishing process. For example, patent application CN202221956910.3 discloses an outdoor water-repellent and antibacterial sun protection clothing fabric, in which the sun protection function is derived from the anti-ultraviolet coating applied on the surface of the fabric. Similarly, patent applications CN202021370938.X and patent applications CN202121910647.X also achieve sun protection functions by applying anti-ultraviolet coatings. Although the sun protection effect of these fabrics is significant, their air permeability and moisture permeability are poor, and the wearing experience is not good.
[0004] In order to improve the air permeability and moisture permeability of sun-proof clothing, patent application CN202222192491.7 discloses a shaped fiber monofilament and shaped yarn, sun-proof fabric and sun-proof clothing. The cross section of the shaped fiber monofilament used is three parallel circular structures to increase the air permeability and moisture absorption of the fabric. However, the anti-ultraviolet ability of this shaped fiber is relatively weak, which is difficult to meet the high requirements of people for sun-proof clothing in the hot summer.
[0005] Therefore, there is an urgent need for a fabric that has both good UV resistance and air permeability to meet people's demand for sun protection clothing. Summary of the invention
[0006] The purpose of the invention is to solve the problems existing in the prior art and provide a method for preparing raw yarn sunscreen clothing fabric.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a raw yarn sunscreen clothing fabric, comprising spinning a spinning melt containing 12-15 wt% of coated modified titanium dioxide, and performing 5-6 times drafting during the spinning process to obtain sunscreen fibers, spinning the sunscreen fibers into sunscreen yarns, and then weaving the sunscreen yarns into fabrics, thereby obtaining the raw yarn sunscreen clothing fabric;
[0009] The D50 particle size (i.e., median diameter or median particle size) of the coated modified titanium dioxide is 50~900nm;
[0010] The coated modified titanium dioxide includes titanium dioxide and polyester oligomers coated on the surface thereof by covalent bonds, wherein the polyester oligomers and the matrix of the spinning melt are different only in average degree of polymerization, and the average degree of polymerization of the polyester oligomers is 20-60;
[0011] Spinning uses a hollow special-shaped spinneret.
[0012] As the preferred technical solution:
[0013] In the above-mentioned method for preparing a raw yarn sunscreen clothing fabric, the thickness of the polyester oligomer on the surface of titanium dioxide is 10-100 nm.
[0014] The preparation method of the raw yarn sunscreen clothing fabric as described above, the preparation method of the coated modified titanium dioxide is: firstly, titanium dioxide is organically modified by a coupling agent to obtain coupling agent modified titanium dioxide, and polyester oligomers are prepared at the same time, and then the polyester oligomers and coupling agent modified titanium dioxide are mixed and reacted.
[0015] In the method for preparing a raw yarn sunscreen clothing fabric as described above, the coupling agent is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane; the mass of the coupling agent is 3-5% of the mass of titanium dioxide; the organic modification is completed in a high-speed blender at a speed of 2500-3000 r / min, a temperature of 80-100°C, and a time of 2-3 hours.
[0016] The preparation method of the raw yarn sunscreen clothing fabric as described above, the preparation steps of the coated modified titanium dioxide are as follows:
[0017] (a) organically modifying titanium dioxide with a coupling agent to obtain coupling agent-modified titanium dioxide;
[0018] (b) adding the dibasic acid and the diol into a reaction kettle, stirring and heating to 200-230° C., controlling the pressure of the reaction system to 0.2-0.3 MPa, reacting for 3-5 hours, then adding a catalyst, controlling the temperature of the reaction system to gradually rise to 260-270° C., evacuating to a vacuum degree of less than 80 Pa, reacting for 2-3 hours, and then cooling to 230° C. to obtain a polyester oligomer;
[0019] (c) adding the coupling agent modified titanium dioxide to the reaction system of step (b), stirring to fully mix, keeping the temperature for reaction for 0.5 to 1 hour, continuously evacuating the vacuum, discharging, cooling, pre-crushing, and airflow crushing to obtain coated modified titanium dioxide;
[0020] The dibasic acid is terephthalic acid; the diol is one or more of ethylene glycol, propylene glycol and butanediol.
[0021] In the method for preparing a raw yarn sunscreen clothing fabric as described above, the molar ratio of the dibasic acid to the diol is 1:0.9-0.95; the mass of the catalyst is 0.01-0.1% of the mass of the dibasic acid; and the mass ratio of the coupling agent-modified titanium dioxide to the polyester oligomer is 5-8:1.
[0022] According to the method for preparing a raw yarn sunscreen clothing fabric as described above, the preparation process of the spinning melt is: first, resin A and coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 50~65wt%, and then the masterbatch is melt-blended with resin B through a single-screw extruder to obtain a spinning melt, wherein resin A and resin B are the same substance, the aspect ratio of the screw is 25~30:1, and the temperature of the first to fifth zones of the single-screw extruder is 240~280℃.
[0023] The method for preparing the raw yarn sunscreen clothing fabric as described above, the production process of the sunscreen fiber is as follows: the spinning melt is extruded from the hollow special-shaped spinneret → primary cooling → primary winding → secondary cooling → oiling → drafting → false deformation → heat setting → secondary winding;
[0024] The cold air temperature used for primary cooling is 15~25℃; the speed of primary winding is 800~1200m / min; secondary cooling refers to storage for 24h at a temperature of 20~30℃ and a relative humidity of 60~70%; the oil concentration used for oiling is 10~18wt%, and the oil wheel speed is 4~6 rpm; the drawing speed is 780~850m / min, and the drawing temperature is 80~120℃; false twist deformation is carried out on a texturing machine, the speed ratio (D / Y) is 1.5~1.7, the temperature of the first hot box is 150~180℃, and the temperature of the second hot box is 120~130℃; the heat setting temperature is 135~145℃; the speed of secondary winding is 4500~4600m / min.
[0025] According to the method for preparing the raw yarn sunscreen clothing fabric as described above, the specification of the sunscreen fiber is 20~50D / 12~36F; the specification of the sunscreen yarn is 20~50 metric deniers; the raw yarn sunscreen clothing fabric is a knitted fabric, the number of needles of the circular knitting machine is 40G, and the gram weight is 150~300g / m 2; Or, the raw yarn sunscreen clothing fabric is a woven plain fabric with a warp density of 120-130 strands / 10cm, a weft density of 130-150 strands / 10cm, and a gram weight of 40-300g / m 2 Or, the raw yarn sunscreen clothing fabric is a woven twill fabric with a warp density of 120-190 strands / 10cm, a weft density of 140-150 strands / 10cm, and a gram weight of 60-300g / m 2 The UPF value of the original yarn sun protection clothing fabric is 50~1300, the UPF value change rate after washing 30 times is no more than 5%, the water droplet diffusion time is 1~2s, the water absorption rate is 105~120%, the maximum diffusion radius is 25~30mm, the diffusion speed is>4mm / s, and the 100% water content tensile force rise rate (used to characterize the viscosity between the fabric and the skin when wet) does not exceed 20%.
[0026] Principle of the invention:
[0027] In the preparation process of the hollow shaped fiber of the present invention, the coated modified titanium dioxide with a specific particle size is densely distributed in the resin matrix. During the spinning process, the fiber is subjected to a high multiple drafting (5 to 6 times). While the fiber is being refined, the coated modified titanium dioxide is squeezed against each other during the fiber drafting process. The coated modified titanium dioxide is respectively gathered and exposed to the inner surface and the outer surface of the hollow fiber, thereby forming a large number of convex structures (such as Figure 1 As shown), these raised structures resemble dot arrays.
[0028] For the outer surface of the hollow shaped fiber, a large number of convex structures make most of the light fall on the convexities. The convexities are formed by the coated modified titanium dioxide. Since the coated modified titanium dioxide has a strong scattering effect on ultraviolet rays, most of the ultraviolet rays can be scattered by the coated modified titanium dioxide and cannot irradiate the human skin, while the unscattered ultraviolet rays will enter the hollow shaped fiber. Since a large number of convex structures are also distributed on the inner surface of the hollow shaped fiber, the ultraviolet rays entering the hollow shaped fiber will be further scattered and reflected on the inner surface of the hollow shaped fiber. The scattered part of the ultraviolet rays cannot penetrate the fabric to reach the human skin, and the reflected part will be scattered again between the coated modified titanium dioxide inside the hollow shaped fiber, thereby giving the hollow shaped fiber raw yarn a sunscreen function.
[0029] At the same time, the hollow shaped fibers of the present invention can be woven to obtain raw yarn sunscreen clothing fabrics. For the inner side of the fabric, a large number of convex structures on the outer surface of the hollow shaped fibers can reduce the contact area between the fabric and the skin, and can prevent the fabric from sticking to the skin and causing physical discomfort when sweating a lot. At the same time, a large number of grooves are formed between the convexities on the surface of the same hollow shaped fiber, which is conducive to the rapid spreading of water on the fiber surface. A large number of capillary-like channels are formed between the convexities of different hollow shaped fibers, which is conducive to the rapid conduction of water, further improving the moisture conduction function of the fabric, so that the fabric can achieve the functions of wet non-stick, anti-permeability and quick-drying, which can greatly improve the comfort of the human body.
[0030] Beneficial effects:
[0031] (1) The present invention introduces a large amount of coated modified titanium dioxide into the hollow shaped fiber, and effectively blocks ultraviolet rays from irradiating human skin by virtue of the strong scattering effect of titanium dioxide on ultraviolet rays. At the same time, by coating and modifying the titanium dioxide, the titanium dioxide is not easily lost during the washing process, thereby ensuring that the UPF value of the fabric does not change significantly after multiple washings, thereby achieving long-lasting sun protection.
[0032] (2) The hollow shaped fibers and fabrics woven therefrom of the present invention have a large number of protruding structures distributed on both the inner and outer surfaces of the fibers, which not only enhances the anti-ultraviolet performance, but also significantly improves the air permeability and moisture permeability of the fabric. When worn, the fabric can quickly absorb and diffuse sweat, keep the skin dry, and improve wearing comfort. It has the characteristics of being non-sticky, anti-permeable, and quick-drying. Even in the case of heavy sweating, the fabric will not stick to the skin. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the structure of the sun-protection fiber of Example 1; wherein a is a cross section and b is a profile. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0035] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:
[0036] Average degree of polymerization: tested by gel permeation chromatography (GPC).
[0037] UPF value: Tested in accordance with GB / T 18830-2009.
[0038] Washing: Tested in accordance with GB / T 8629-2001.
[0039] Water droplet diffusion time: Tested with reference to 8.2 Water droplet diffusion time in GB / T 21655.1-2023.
[0040] Water absorption: Test according to 8.1 water absorption test method in GB / T 21655.1-2023.
[0041] Maximum diffusion radius and diffusion rate: Cut the sample to be tested into a sheet specimen of 10cm×10cm, and carry out a water drop test according to 8.21-8.23 of GB / T21655.1-2023. Start timing from the moment the water drop contacts the surface of the sample (recorded as t0, unit s), and stop timing when the water stops spreading on the outermost side of the wetting circle on the sample (recorded as t, unit s). Measure the distances from three different points on the outermost side of the wetting circle to the center point within 30s, and the arithmetic average of the three values is recorded as the maximum diffusion radius (unit mm); diffusion rate = maximum diffusion radius / (t-t0).
[0042] 100% moisture content tensile force rise rate: the samples to be tested are cut into 6 20cm×5cm sheet specimens, which are divided into Group A and Group B, with 3 specimens in each group. The specimens in Group A and Group B are subjected to moisture treatment under the conditions of temperature 29℃±0.2℃ and ambient humidity 65%±2% respectively: the specimens in Group A are subjected to 100% moisture treatment, and the specimens in Group B are subjected to 0% moisture treatment respectively; the specific process of 100% moisture treatment is: the specimens are continuously humidified by using a humidifier until the weight gain of the fabric reaches 100% of its original weight; the specific process of 0% moisture treatment is: the specimens are placed in a vacuum drying oven at 60℃ for drying until the moisture content of the specimens is 0%;
[0043] Subsequently, the 100% water content tension and 0% water content tension were tested respectively. The specific process was as follows: select a subject, use a marker to mark two marking lines on the subject's forearm (5cm and 10cm away from the elbow), use iron clamps to clamp the two short sides of the fabric sample respectively, and the subject keeps the forearm horizontal, and puts the sample between the two marked lines, with both ends of the sample hanging naturally. After that, hang a 25g weight on one end of the sample and connect the other end to a spring scale. After adjusting the spring scale to zero, slowly pull the spring scale until the sample starts to slide on the forearm. At the moment the sample slides, quickly record the tension data on the spring scale. The average value of the tension data of the samples in Group A is the 100% water content tension (recorded as F 100% , unit N), the average value of the tensile force data of the samples in group B is the 0% water content tensile force (denoted as F 0%, unit N); all tests were completed on the same subject's arm, and the subject's arm was wiped dry between each test;
[0044] Finally, the 100% water content tensile force increase rate of the sample to be tested is calculated by the following formula:
[0045] 100% water content tensile force increase rate = (F 100% -F 0% ) / F 0% .
[0046] Example 1
[0047] A method for preparing a raw yarn sunscreen clothing fabric, the specific steps are as follows:
[0048] (1) Preparation of raw materials;
[0049] Coupling agent: γ-aminopropyltriethoxysilane;
[0050] Titanium dioxide;
[0051] Dibasic acid: terephthalic acid;
[0052] Diol: ethylene glycol;
[0053] Catalyst: Antimony glycol;
[0054] Resin A and Resin B: both are polyester (PET) with an average degree of polymerization of 600;
[0055] (2) Preparation of coated modified titanium dioxide;
[0056] (2.1) In a high-speed blender, at a speed of 3000 r / min and a temperature of 80°C, titanium dioxide is organically modified with a coupling agent for 2.5 hours to obtain coupling agent-modified titanium dioxide; wherein the mass of the coupling agent is 5% of the mass of the titanium dioxide;
[0057] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 200°C, control the pressure of the reaction system to 0.2MPa, react for 4.5h, then add the catalyst, control the reaction system to gradually heat to 260°C, evacuate to 75Pa, react for 2.2h, and then cool to 230°C to obtain a polyester oligomer with an average degree of polymerization of 20; wherein the molar ratio of the dibasic acid to the diol is 1:0.95, and the mass of the catalyst is 0.01% of the mass of the dibasic acid;
[0058] (2.3) adding coupling agent modified titanium dioxide to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 0.5h, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified titanium dioxide; wherein the mass ratio of coupling agent modified titanium dioxide to polyester oligomer is 5:1;
[0059] The prepared coated modified titanium dioxide includes titanium dioxide and polyester oligomer, and the polyester oligomer is coated on the surface of titanium dioxide through a coupling agent; the D50 particle size of the coated modified titanium dioxide is 600nm, and the thickness of the polyester oligomer on the surface of titanium dioxide is 60nm;
[0060] (3) preparing a spinning melt;
[0061] First, resin A and coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 55wt%, and then the masterbatch is melt-blended with resin B through a single screw extruder to obtain a spinning melt containing 13wt% of coated modified titanium dioxide; wherein the aspect ratio of the screw is 25:1, and the temperatures of zones 1 to 5 of the single screw extruder are 240°C, 245°C, 265°C, 280°C, and 280°C, respectively;
[0062] (4) Preparation of sunscreen fibers;
[0063] The production process of sunscreen fiber is as follows: spinning melt is extruded from a hollow special-shaped spinneret → cooling → primary winding → storage → oiling → drafting → false twisting (performed on a texturing machine) → heat setting → secondary winding;
[0064] The cold air temperature used for cooling is 15℃; the speed of the first winding is 800m / min; the storage temperature is 20℃, the relative humidity is 65%, and the storage time is 24h; the oil concentration used for oiling is 12wt%, and the oil wheel speed is 5 rpm; the drafting speed is 780m / min, the drafting temperature is 85℃, and the drafting multiple is 5 times; the speed ratio of false twist deformation is 1.5, the temperature of the first hot box is 150℃, and the temperature of the second hot box is 120℃; the heat setting temperature is 135℃; the speed of the second winding is 4500m / min;
[0065] The specification of the prepared sunscreen fiber is 20D / 12F, and the structure of the sunscreen fiber is as follows: Figure 1 As shown;
[0066] (5) Preparation of raw yarn sunscreen clothing fabrics;
[0067] The sun-proof fiber is spun into sun-proof yarn with a specification of 25 metric deniers, and then the sun-proof yarn is woven into fabric to obtain the raw yarn sun-proof clothing fabric.
[0068] The final raw yarn sunscreen clothing fabric is a knitted fabric, the circular knitting machine needle count is 40G, and the gram weight is 150g / m 2 The UPF value of the original yarn sun protection clothing fabric is 260. The UPF value change rate after washing 30 times is 2.2%. The water droplet diffusion time is 1.5s, the water absorption rate is 118%, the maximum diffusion radius is 28.2mm, the diffusion speed is 4.8mm / s, and the 100% water content tensile force increase rate is 14.8%.
[0069] Comparative Example 1
[0070] A method for preparing a fabric is basically the same as that in Example 1, except that the content of the coated modified titanium dioxide in the spinning melt obtained in step (3) is 10 wt%.
[0071] The final fabric has a UPF value of 80, a water droplet diffusion time of 2.8s, a water absorption rate of 94%, a maximum diffusion radius of 17.3mm, a diffusion speed of 2.4mm / s, and a 100% water content tensile force increase rate of 86%.
[0072] Compared with Example 1, the anti-ultraviolet performance and air permeability and moisture permeability of the fabric of Comparative Example 1 are significantly reduced. This is because the addition amount of the coated modified titanium dioxide in Comparative Example 1 is too low, so that the distribution density of the coated modified titanium dioxide in the resin matrix is low. During the drawing process, the degree of mutual extrusion between the particles is weak, and it is impossible to promote enough coated modified titanium dioxide to fully gather and expose to the inner and outer surfaces of the hollow special-shaped fibers, and thus it is difficult to form a convex structure similar to a point array;
[0073] From the perspective of anti-ultraviolet performance, due to the insufficient number of protrusions on the outer surface, the proportion of light falling on the protrusions composed of coated modified titanium dioxide is greatly reduced, and the effect of blocking ultraviolet rays by relying on the strong scattering effect of coated modified titanium dioxide on ultraviolet rays is weakened. More ultraviolet rays can penetrate the fabric, resulting in a decrease in the fabric's anti-ultraviolet ability;
[0074] In terms of air permeability and moisture permeability, since the protrusion structure on the fiber surface is not rich enough, the number of grooves formed between the protrusions on the surface of the same hollow shaped fiber and the capillary-like channels formed between the protrusions of different hollow shaped fibers is limited. When the human body sweats, the sweat cannot be discharged in time and effectively, the air permeability and moisture permeability of the fabric deteriorates, and the functions of wet-non-stick, anti-permeability and quick-drying cannot be well achieved.
[0075] Comparative Example 2
[0076] A method for preparing a fabric is basically the same as that of Example 1, except that the process parameters of pre-crushing and air flow crushing are adjusted in step (2.3) so that the D50 particle size of the coated modified titanium dioxide is 40 nm.
[0077] The final fabric has a UPF value of 120, a water droplet diffusion time of 2.6s, a water absorption rate of 88%, a maximum diffusion radius of 13.5mm, a diffusion speed of 2.2mm / s, and a 100% water content tensile force increase rate of 102%.
[0078] Compared with Example 1, the anti-ultraviolet performance and air and moisture permeability of the fabric in Comparative Example 2 are significantly reduced. This is because the particle size of the coated modified titanium dioxide in Comparative Example 2 is too small, and it is difficult to gather and expose to the inner and outer surfaces of the fiber in an orderly manner under mutual squeezing during the stretching process to form a convex structure similar to a point array, resulting in the deterioration of the anti-ultraviolet performance and air and moisture permeability of the fabric.
[0079] Comparative Example 3
[0080] A method for preparing a fabric is basically the same as that of Example 1, except that in step (4), the drafting multiple is 4.5 times.
[0081] The final fabric has a UPF value of 135, a water droplet diffusion time of 3.1s, a water absorption rate of 86%, a maximum diffusion radius of 13.3mm, a diffusion speed of 2.1mm / s, and a 100% water content tensile force increase rate of 108%.
[0082] Compared with Example 1, the anti-ultraviolet performance and air permeability and moisture permeability of the fabric in Comparative Example 3 are significantly reduced. This is because the drafting in Comparative Example 3 is insufficient, and the strength and effect of the mutual squeezing between the particles are poor, resulting in a reduction in the amount of coated modified titanium dioxide aggregated and exposed on the inner and outer surfaces of the fiber, making it difficult to form a convex structure, resulting in the deterioration of the anti-ultraviolet performance and air permeability and moisture permeability of the fabric.
[0083] Comparative Example 4
[0084] A method for preparing a fabric is basically the same as that of Example 1, except that the hollow special-shaped spinneret is replaced by a common round-hole spinneret.
[0085] The final fabric has a UPF value of 40, a water droplet diffusion time of 1.6s, a water absorption rate of 108%, a maximum diffusion radius of 28.0mm, a diffusion speed of 4.5mm / s, and a 100% water content tensile force increase rate of 15.2%.
[0086] Compared with Example 1, the anti-ultraviolet performance and air and moisture permeability of the fabric in Comparative Example 4 are significantly reduced. This is because the ordinary round-hole spinneret used in Comparative Example 4 makes it difficult for the coated modified titanium dioxide with a specific particle size to squeeze each other during fiber drawing and aggregate and expose to the inner and outer surfaces to form a large number of protrusion structures (similar to a point array) during the spinning process, resulting in the deterioration of the anti-ultraviolet performance and air and moisture permeability of the fabric.
[0087] Example 2
[0088] A method for preparing a raw yarn sunscreen clothing fabric, the specific steps are as follows:
[0089] (1) Preparation of raw materials;
[0090] Coupling agent: γ-aminopropyltriethoxysilane;
[0091] Titanium dioxide;
[0092] Dibasic acid: terephthalic acid;
[0093] Diol: Propylene glycol;
[0094] Catalyst: Antimony glycol;
[0095] Resin A and Resin B: both are polyester (PET) with an average degree of polymerization of 720;
[0096] (2) Preparation of coated modified titanium dioxide;
[0097] (2.1) In a high-speed blender, at a speed of 2800 r / min and a temperature of 100° C., titanium dioxide is organically modified with a coupling agent for 2.8 hours to obtain coupling agent-modified titanium dioxide; wherein the mass of the coupling agent is 3% of the mass of the titanium dioxide;
[0098] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 210°C, control the pressure of the reaction system to 0.2MPa, react for 3.5h, then add the catalyst, control the reaction system to gradually heat up to 265°C, evacuate to 68Pa, react for 2.6h, and then cool to 230°C to obtain a polyester oligomer with an average degree of polymerization of 32; wherein the molar ratio of the dibasic acid to the diol is 1:0.92, and the mass of the catalyst is 0.04% of the mass of the dibasic acid;
[0099] (2.3) adding coupling agent modified titanium dioxide to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 0.5h, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified titanium dioxide; wherein the mass ratio of coupling agent modified titanium dioxide to polyester oligomer is 6:1;
[0100] The prepared coated modified titanium dioxide includes titanium dioxide and polyester oligomer, and the polyester oligomer is coated on the surface of titanium dioxide through a coupling agent; the D50 particle size of the coated modified titanium dioxide is 300nm, and the thickness of the polyester oligomer on the surface of titanium dioxide is 30nm;
[0101] (3) preparing a spinning melt;
[0102] First, resin A and coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 52wt%, and then the masterbatch is melt-blended with resin B through a single screw extruder to obtain a spinning melt containing 13wt% of coated modified titanium dioxide; wherein the aspect ratio of the screw is 28:1, and the temperatures of zones 1 to 5 of the single screw extruder are 240°C, 245°C, 265°C, 280°C, and 280°C, respectively;
[0103] (4) Preparation of sunscreen fibers;
[0104] The production process of sunscreen fiber is as follows: spinning melt is extruded from a hollow special-shaped spinneret → cooling → primary winding → storage → oiling → drafting → false twisting (performed on a texturing machine) → heat setting → secondary winding;
[0105] The cold air temperature used for cooling is 20℃; the speed of the first winding is 850m / min; the storage temperature is 20℃, the relative humidity is 60%, and the storage time is 24h; the oil concentration used for oiling is 15wt%, and the oil wheel speed is 4 rpm; the drafting speed is 800m / min, the drafting temperature is 80℃, and the drafting multiple is 5.2 times; the speed ratio of false twist deformation is 1.6, the temperature of the first hot box is 150℃, and the temperature of the second hot box is 130℃; the heat setting temperature is 138℃; the speed of the second winding is 4550m / min;
[0106] The specification of the produced sunscreen fiber is 50D / 36F;
[0107] (5) Preparation of raw yarn sunscreen clothing fabrics;
[0108] The sun-proof fiber is spun into sun-proof yarn with a specification of 33 metric denier, and then the sun-proof yarn is woven into fabric to obtain the raw yarn sun-proof clothing fabric.
[0109] The final raw yarn sunscreen clothing fabric is a knitted fabric, the circular knitting machine needle count is 40G, and the gram weight is 300g / m 2 The UPF value of the original yarn sun protection clothing fabric is 390, the UPF value change rate after washing 30 times is 3.4%, the water droplet diffusion time is 1.6s, the water absorption rate is 109%, the maximum diffusion radius is 25.3mm, the diffusion speed is 4.2mm / s, and the 100% water content tensile force increase rate is 9.5%.
[0110] Example 3
[0111] A method for preparing a raw yarn sunscreen clothing fabric, the specific steps are as follows:
[0112] (1) Preparation of raw materials;
[0113] Coupling agent: γ-aminopropyltriethoxysilane;
[0114] Titanium dioxide;
[0115] Dibasic acid: terephthalic acid;
[0116] Diol: ethylene glycol;
[0117] Catalyst: tetrabutyl titanate;
[0118] Resin A and Resin B: both are polyester (PET) with an average degree of polymerization of 600;
[0119] (2) Preparation of coated modified titanium dioxide;
[0120] (2.1) In a high-speed blender, at a speed of 2500 r / min and a temperature of 100°C, titanium dioxide is organically modified with a coupling agent for 2 hours to obtain coupling agent-modified titanium dioxide; wherein the mass of the coupling agent is 3.5% of the mass of the titanium dioxide;
[0121] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 220°C, control the pressure of the reaction system to 0.25MPa, react for 3h, then add the catalyst, control the reaction system to gradually heat to 270°C, evacuate to 72Pa, react for 2h, and then cool to 230°C to obtain a polyester oligomer with an average degree of polymerization of 42; wherein the molar ratio of the dibasic acid to the diol is 1:0.9, and the mass of the catalyst is 0.06% of the mass of the dibasic acid;
[0122] (2.3) adding coupling agent modified titanium dioxide to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 1 hour, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified titanium dioxide; wherein the mass ratio of coupling agent modified titanium dioxide to polyester oligomer is 8:1;
[0123] The prepared coated modified titanium dioxide includes titanium dioxide and polyester oligomer, and the polyester oligomer is coated on the surface of titanium dioxide through a coupling agent; the D50 particle size of the coated modified titanium dioxide is 150nm, and the thickness of the polyester oligomer on the surface of titanium dioxide is 10nm;
[0124] (3) preparing a spinning melt;
[0125] First, resin A and coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 50wt%, and then the masterbatch is melt-blended with resin B through a single screw extruder to obtain a spinning melt containing 12wt% coated modified titanium dioxide; wherein the aspect ratio of the screw is 30:1, and the temperatures of zones 1 to 5 of the single screw extruder are 240°C, 245°C, 265°C, 280°C, and 280°C, respectively;
[0126] (4) Preparation of sunscreen fibers;
[0127] The production process of sunscreen fiber is as follows: spinning melt is extruded from a hollow special-shaped spinneret → cooling → primary winding → storage → oiling → drafting → false twisting (performed on a texturing machine) → heat setting → secondary winding;
[0128] The cold air temperature used for cooling is 20℃; the speed of the first winding is 1200m / min; the storage temperature is 25℃, the relative humidity is 63%, and the storage time is 24h; the oil concentration used for oiling is 10wt%, and the oil wheel speed is 5 rpm; the drawing speed is 820m / min, the drawing temperature is 110℃, and the drawing multiple is 6 times; the speed ratio of false twist deformation is 1.6, the temperature of the first hot box is 165℃, and the temperature of the second hot box is 128℃; the heat setting temperature is 142℃; the speed of the second winding is 4580m / min;
[0129] The specification of the produced sun-protective fiber is 30D / 24F;
[0130] (5) Preparation of raw yarn sunscreen clothing fabrics;
[0131] The sun-proof fiber is spun into sun-proof yarn with a specification of 46 metric denier, and then the sun-proof yarn is woven into fabric to obtain the raw yarn sun-proof clothing fabric.
[0132] The final raw yarn sunscreen clothing fabric is a woven plain fabric with a warp density of 120 strands / 10cm, a weft density of 150 strands / 10cm, and a gram weight of 40g / m 2 The UPF value of the original yarn sun protection clothing fabric is 50. The UPF value change rate after washing 30 times is 1.8%, the water droplet diffusion time is 1.8s, the water absorption rate is 120%, the maximum diffusion radius is 29.4mm, the diffusion speed is 5mm / s, and the 100% water content tensile force increase rate is 15.7%.
[0133] Example 4
[0134] A method for preparing a raw yarn sunscreen clothing fabric, the specific steps are as follows:
[0135] (1) Preparation of raw materials;
[0136] Coupling agent: γ-aminopropyltrimethoxysilane;
[0137] Titanium dioxide;
[0138] Dibasic acid: terephthalic acid;
[0139] Diol: Butanediol;
[0140] Catalyst: tetrabutyl titanate;
[0141] Resin A and Resin B: both are polyester (PET) with an average degree of polymerization of 720;
[0142] (2) Preparation of coated modified titanium dioxide;
[0143] (2.1) In a high-speed blender, at a speed of 2500 r / min and a temperature of 90°C, titanium dioxide is organically modified with a coupling agent for 3 hours to obtain coupling agent-modified titanium dioxide; wherein the mass of the coupling agent is 4.5% of the mass of the titanium dioxide;
[0144] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 230°C, control the pressure of the reaction system to 0.25MPa, react for 4h, then add the catalyst, control the reaction system to gradually heat to 270°C, evacuate to 78Pa, react for 2.8h, and then cool to 230°C to obtain a polyester oligomer with an average degree of polymerization of 60; wherein the molar ratio of the dibasic acid to the diol is 1:0.93, and the mass of the catalyst is 0.1% of the mass of the dibasic acid;
[0145] (2.3) adding coupling agent modified titanium dioxide to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 1 hour, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified titanium dioxide; wherein the mass ratio of coupling agent modified titanium dioxide to polyester oligomer is 6:1;
[0146] The prepared coated modified titanium dioxide includes titanium dioxide and polyester oligomer, and the polyester oligomer is coated on the surface of titanium dioxide through a coupling agent; the D50 particle size of the coated modified titanium dioxide is 50nm, and the thickness of the polyester oligomer on the surface of titanium dioxide is 10nm;
[0147] (3) preparing a spinning melt;
[0148] First, resin A and coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 60wt%, and then the masterbatch is melt-blended with resin B through a single screw extruder to obtain a spinning melt containing 13.5wt% of coated modified titanium dioxide; wherein the aspect ratio of the screw is 30:1, and the temperatures of zones 1 to 5 of the single screw extruder are 240°C, 245°C, 265°C, 280°C, and 280°C, respectively;
[0149] (4) Preparation of sunscreen fibers;
[0150] The production process of sunscreen fiber is as follows: spinning melt is extruded from a hollow special-shaped spinneret → cooling → primary winding → storage → oiling → drafting → false twisting (performed on a texturing machine) → heat setting → secondary winding;
[0151] The cold air temperature used for cooling is 25℃; the speed of the first winding is 1000m / min; the storage temperature is 25℃, the relative humidity is 68%, and the storage time is 24h; the oil concentration used for oiling is 15wt%, and the oil wheel speed is 6 rpm; the drafting speed is 850m / min, the drafting temperature is 120℃, and the drafting multiple is 6 times; the speed ratio of false twist deformation is 1.7, the temperature of the first hot box is 180℃, and the temperature of the second hot box is 130℃; the heat setting temperature is 145℃; the speed of the second winding is 4600m / min;
[0152] The specification of the produced sunscreen fiber is 20D / 12F;
[0153] (5) Preparation of raw yarn sunscreen clothing fabrics;
[0154] The sun-proof fiber is spun into sun-proof yarn with a specification of 50 metric deniers, and then the sun-proof yarn is woven into fabric to obtain the raw yarn sun-proof clothing fabric.
[0155] The final raw yarn sunscreen clothing fabric is a woven plain fabric with a warp density of 130 strands / 10cm, a weft density of 130 strands / 10cm, and a gram weight of 300g / m 2 The UPF value of the original yarn sun protection clothing fabric is 1100. The UPF value change rate after washing 30 times is 3.9%. The water droplet diffusion time is 1.4s, the water absorption rate is 107%, the maximum diffusion radius is 26.4mm, the diffusion speed is 4.3mm / s, and the 100% water content tensile force increase rate is 12.3%.
[0156] Example 5
[0157] A method for preparing a raw yarn sunscreen clothing fabric, the specific steps are as follows:
[0158] (1) Preparation of raw materials;
[0159] Coupling agent: γ-aminopropyltrimethoxysilane;
[0160] Titanium dioxide;
[0161] Dibasic acid: terephthalic acid;
[0162] Diol: a mixture of ethylene glycol and propylene glycol in a molar ratio of 1:1;
[0163] Catalyst: Antimony glycol;
[0164] Resin A and Resin B: both are polyester (PET) with an average degree of polymerization of 600;
[0165] (2) Preparation of coated modified titanium dioxide;
[0166] (2.1) In a high-speed blender, at a speed of 3000 r / min and a temperature of 90°C, titanium dioxide is organically modified with a coupling agent for 2.5 hours to obtain coupling agent-modified titanium dioxide; wherein the mass of the coupling agent is 4% of the mass of the titanium dioxide;
[0167] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 225°C, control the pressure of the reaction system to 0.3MPa, react for 5h, then add the catalyst, control the reaction system to gradually heat up to 265°C, evacuate to 76Pa, react for 3h, and then cool to 230°C to obtain a polyester oligomer with an average degree of polymerization of 56; wherein the molar ratio of the dibasic acid to the diol is 1:0.91, and the mass of the catalyst is 0.08% of the mass of the dibasic acid;
[0168] (2.3) adding coupling agent modified titanium dioxide to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 1 hour, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified titanium dioxide; wherein the mass ratio of coupling agent modified titanium dioxide to polyester oligomer is 5:1;
[0169] The prepared coated modified titanium dioxide includes titanium dioxide and polyester oligomer, and the polyester oligomer is coated on the surface of titanium dioxide through a coupling agent; the D50 particle size of the coated modified titanium dioxide is 750nm, and the thickness of the polyester oligomer on the surface of titanium dioxide is 50nm;
[0170] (3) preparing a spinning melt;
[0171] First, resin A and coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 65wt%, and then the masterbatch is melt-blended with resin B through a single screw extruder to obtain a spinning melt containing 15wt% of coated modified titanium dioxide; wherein the aspect ratio of the screw is 28:1, and the temperatures of zones 1 to 5 of the single screw extruder are 240°C, 245°C, 265°C, 280°C, and 280°C, respectively;
[0172] (4) Preparation of sunscreen fibers;
[0173] The production process of sunscreen fiber is as follows: spinning melt is extruded from a hollow special-shaped spinneret → cooling → primary winding → storage → oiling → drafting → false twisting (performed on a texturing machine) → heat setting → secondary winding;
[0174] The cold air temperature used for cooling is 23℃; the speed of the first winding is 900m / min; the storage temperature is 30℃, the relative humidity is 70%, and the storage time is 24h; the oil concentration used for oiling is 13wt%, and the oil wheel speed is 5 rpm; the drafting speed is 800m / min, the drafting temperature is 115℃, and the drafting multiple is 5.6 times; the speed ratio of false twist deformation is 1.5, the temperature of the first hot box is 170℃, and the temperature of the second hot box is 125℃; the heat setting temperature is 145℃; the speed of the second winding is 4600m / min;
[0175] The specification of the produced sunscreen fiber is 50D / 12F;
[0176] (5) Preparation of raw yarn sunscreen clothing fabrics;
[0177] The sun-proof fiber is spun into sun-proof yarn with a specification of 30 metric deniers, and then the sun-proof yarn is woven into fabric to obtain the raw yarn sun-proof clothing fabric.
[0178] The final raw yarn sunscreen clothing fabric is a woven twill fabric with a warp density of 120 strands / 10cm, a weft density of 150 strands / 10cm, and a gram weight of 60g / m 2 The UPF value of the original yarn sun protection clothing fabric is 420, the UPF value change rate after washing 30 times is 2.6%, the water droplet diffusion time is 1.2s, the water absorption rate is 116%, the maximum diffusion radius is 29.8mm, the diffusion speed is 5.2mm / s, and the 100% water content tensile force increase rate is 18.9%.
[0179] Example 6
[0180] A method for preparing a raw yarn sunscreen clothing fabric, the specific steps are as follows:
[0181] (1) Preparation of raw materials;
[0182] Coupling agent: γ-aminopropyltrimethoxysilane;
[0183] Titanium dioxide;
[0184] Dibasic acid: terephthalic acid;
[0185] Diol: a mixture of ethylene glycol and butanediol in a molar ratio of 1:1;
[0186] Catalyst: tetrabutyl titanate;
[0187] Resin A and Resin B: both are polyester (PET) with an average degree of polymerization of 720;
[0188] (2) Preparation of coated modified titanium dioxide;
[0189] (2.1) In a high-speed blender, at a speed of 3000 r / min and a temperature of 85°C, titanium dioxide is organically modified with a coupling agent for 3 hours to obtain coupling agent-modified titanium dioxide; wherein the mass of the coupling agent is 4% of the mass of the titanium dioxide;
[0190] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 220°C, control the pressure of the reaction system to 0.3MPa, react for 5h, then add the catalyst, control the reaction system to gradually heat to 260°C, evacuate to 70Pa, react for 2.5h, and then cool to 230°C to obtain a polyester oligomer with an average degree of polymerization of 39; wherein the molar ratio of the dibasic acid to the diol is 1:0.95, and the mass of the catalyst is 0.05% of the mass of the dibasic acid;
[0191] (2.3) adding coupling agent modified titanium dioxide to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 0.75h, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified titanium dioxide; wherein the mass ratio of coupling agent modified titanium dioxide to polyester oligomer is 7:1;
[0192] The prepared coated modified titanium dioxide includes titanium dioxide and polyester oligomer, and the polyester oligomer is coated on the surface of titanium dioxide through a coupling agent; the D50 particle size of the coated modified titanium dioxide is 900nm, and the thickness of the polyester oligomer on the surface of titanium dioxide is 100nm;
[0193] (3) preparing a spinning melt;
[0194] First, resin A and coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 63wt%, and then the masterbatch is melt-blended with resin B through a single screw extruder to obtain a spinning melt containing 14wt% of coated modified titanium dioxide; wherein the aspect ratio of the screw is 25:1, and the temperatures of zones 1 to 5 of the single screw extruder are 240°C, 245°C, 265°C, 280°C, and 280°C, respectively;
[0195] (4) Preparation of sunscreen fibers;
[0196] The production process of sunscreen fiber is as follows: spinning melt is extruded from a hollow special-shaped spinneret → cooling → primary winding → storage → oiling → drafting → false twisting (performed on a texturing machine) → heat setting → secondary winding;
[0197] The cold air temperature used for cooling is 18℃; the speed of the first winding is 950m / min; the storage temperature is 30℃, the relative humidity is 65%, and the storage time is 24h; the oil concentration used for oiling is 18wt%, and the oil wheel speed is 4.5 rpm; the drafting speed is 790m / min, the drafting temperature is 105℃, and the drafting multiple is 5.5 times; the speed ratio of false twist deformation is 1.7, the first hot box temperature is 175℃, and the second hot box temperature is 125℃; the heat setting temperature is 135℃; the speed of the second winding is 4500m / min;
[0198] The specification of the produced sunscreen fiber is 50D / 24F;
[0199] (5) Preparation of raw yarn sunscreen clothing fabrics;
[0200] The sun-proof fiber is spun into sun-proof yarn with a specification of 20 deniers, and then the sun-proof yarn is woven into fabric to obtain the raw yarn sun-proof clothing fabric.
[0201] The final raw yarn sunscreen clothing fabric is a woven twill fabric with a warp density of 190 strands / 10cm, a weft density of 140 strands / 10cm, and a gram weight of 300g / m 2 The UPF value of the original yarn sun protection clothing fabric is 1300. The UPF value change rate after washing 30 times is 4.2%. The water droplet diffusion time is 1.6s, the water absorption rate is 105%, the maximum diffusion radius is 27.6mm, the diffusion speed is 4.5mm / s, and the 100% water content tensile force increase rate is 13.6%.
Claims
1. A method for preparing raw yarn sunscreen clothing fabric, characterized in that: Spinning a spinning melt containing 12-15 wt% of coated modified titanium dioxide, and performing 5-6 times drafting during the spinning process to obtain a sun-proof fiber, spinning the sun-proof fiber into a sun-proof yarn, and then weaving the sun-proof yarn into a fabric, thereby obtaining an original yarn sun-proof clothing fabric; The D50 particle size of the coated modified titanium dioxide is 50~900nm; The coated modified titanium dioxide includes titanium dioxide and polyester oligomers coated on the surface thereof by covalent bonds, wherein the polyester oligomers and the matrix of the spinning melt are different only in average degree of polymerization, and the average degree of polymerization of the polyester oligomers is 20-60; Spinning uses a hollow special-shaped spinneret.
2. The method for preparing a raw yarn sunscreen clothing fabric according to claim 1, characterized in that: The thickness of polyester oligomers on the titanium dioxide surface is 10~100nm.
3. The method for preparing a raw yarn sunscreen clothing fabric according to claim 2, characterized in that: The preparation method of the coated modified titanium dioxide is as follows: firstly, a coupling agent is used to organically modify titanium dioxide to obtain coupling agent modified titanium dioxide, and simultaneously a polyester oligomer is prepared, and then the polyester oligomer and the coupling agent modified titanium dioxide are mixed and reacted.
4. The method for preparing a raw yarn sunscreen clothing fabric according to claim 3, characterized in that: The coupling agent is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane; the mass of the coupling agent is 3-5% of the mass of titanium dioxide; the organic modification is completed in a high-speed blender at a speed of 2500-3000 r / min, a temperature of 80-100°C, and a time of 2-3 hours.
5. The method for preparing a raw yarn sunscreen clothing fabric according to claim 3, characterized in that: The preparation steps of coated modified titanium dioxide are as follows: (a) organically modifying titanium dioxide with a coupling agent to obtain coupling agent-modified titanium dioxide; (b) adding the dibasic acid and the diol into a reaction kettle, stirring and heating to 200-230° C., controlling the pressure of the reaction system to 0.2-0.3 MPa, reacting for 3-5 hours, then adding a catalyst, controlling the temperature of the reaction system to gradually rise to 260-270° C., evacuating to a vacuum degree of less than 80 Pa, reacting for 2-3 hours, and then cooling to 230° C. to obtain a polyester oligomer; (c) adding the coupling agent modified titanium dioxide to the reaction system of step (b), stirring to fully mix, keeping the temperature for reaction for 0.5 to 1 hour, continuously evacuating the vacuum, discharging, cooling, pre-crushing, and airflow crushing to obtain coated modified titanium dioxide; The dibasic acid is terephthalic acid; the diol is one or more of ethylene glycol, propylene glycol and butanediol.
6. The method for preparing a raw yarn sunscreen clothing fabric according to claim 5, characterized in that: The molar ratio of the dibasic acid to the diol is 1:0.9-0.95; the mass of the catalyst is 0.01-0.1% of the mass of the dibasic acid; and the mass ratio of the coupling agent-modified titanium dioxide to the polyester oligomer is 5-8:
1.
7. The method for preparing a raw yarn sunscreen clothing fabric according to claim 1, characterized in that: The preparation process of the spinning melt is as follows: first, resin A is melt-blended with coated modified titanium dioxide to obtain a masterbatch with a concentration of 50-65wt%, and then the masterbatch is melt-blended with resin B through a single-screw extruder to obtain a spinning melt, wherein resin A and resin B are the same substance, the aspect ratio of the screw is 25-30:1, and the temperature of zones 1 to 5 of the single-screw extruder is 240-280°C.
8. The method for preparing a raw yarn sunscreen clothing fabric according to claim 1, characterized in that: The production process of sunscreen fiber is as follows: spinning melt is extruded from a hollow special-shaped spinneret → primary cooling → primary winding → secondary cooling → oiling → drafting → false deformation → heat setting → secondary winding; The cold air temperature used for primary cooling is 15~25℃; the speed of primary winding is 800~1200m / min; secondary cooling refers to storage for 24h at a temperature of 20~30℃ and a relative humidity of 60~70%; the oil concentration used for oiling is 10~18wt%, and the oil tanker speed is 4~6 rpm; the drawing speed is 780~850m / min, and the drawing temperature is 80~120℃; false twist deformation is carried out on a texturing machine, with a speed ratio of 1.5~1.7, the temperature of the first hot box is 150~180℃, and the temperature of the second hot box is 120~130℃; the heat setting temperature is 135~145℃; the speed of secondary winding is 4500~4600m / min.
9. The method for preparing a raw yarn sunscreen clothing fabric according to claim 1, characterized in that: The specifications of sunscreen fiber are 20~50D / 12~36F; the specifications of sunscreen yarn are 20~50 deniers; the original yarn sunscreen clothing fabric is knitted fabric, the number of circular knitting machines is 40G, and the weight is 150~300g / m 2 ; Or, the raw yarn sunscreen clothing fabric is a woven plain fabric with a warp density of 120-130 strands / 10cm, a weft density of 130-150 strands / 10cm, and a gram weight of 40-300g / m 2 Or, the raw yarn sunscreen clothing fabric is a woven twill fabric with a warp density of 120-190 strands / 10cm, a weft density of 140-150 strands / 10cm, and a gram weight of 60-300g / m 2 The UPF value of the original yarn sun protection clothing fabric is 50~1300. The UPF value change rate after washing 30 times is no more than 5%. The water droplet diffusion time is 1~2s, the water absorption rate is 105~120%, the maximum diffusion radius is 25~30mm, the diffusion speed is >4mm / s, and the 100% water content tensile force increase rate does not exceed 20%.
Citation Information
Patent Citations
Light and thin sunscreen clothing fabric
CN213142346U
Sunscreen fabric
CN216267989U
Outdoor water-repellent antibacterial sunscreen clothing fabric
CN218500053U
Special-shaped fiber monofilament, special-shaped yarn, sunscreen fabric and sunscreen clothes
CN219032479U
Polymer masterbatch for preparing high moisture absorption and high moisture exclusion polyester textile and synthetic method thereof
CN101104729A